Analisis Pengaruh Pendidikan, Pengangguran, Konsumsi Pangan, Kesenjangan Dan Pertumbuhan Ekonomi Terhadap Kemiskinan Di Indonesia - Kesumawardani, Nadia; Syafri, Syafri; Nurhayati, Nurhayati (Fakultas Ekonomi Universitas Gresik, 2023)
To create a prosperous and equitable country, poverty must be handled together. In accordance with the goals of inclusive economic development, that is economic development can create fair access and opportunities for all levels of society, increase welfare and reduce inequality. This study aims to analyze the effect of education, unemployment, inequality, household food consumption and economic growth on poverty rates in Indonesia in 2015-2022, used panel data regression analysis. The result is education has a negative effect on poverty. Unemployment, household food consumption, inequality and economic growth has a positive effect to poverty